Hubungan Pengetahuan HIV/AIDs, Terapi Antiretroviral, dan Infeksi Oportunistik Terhadap Kepatuhan ODHA dalam Menjalani Terapi Antiretroviral - Dikha Ayu Kurnia; Umi Solekhah (Faletehan Health Journal, 2018)
Increasing the number of People Living with HIV / AIDS (PLWHA) is one of the serious global health problems. Antiretroviral (ARV) is the only available therapeutic for PLWHA to be consumed for a lifetime with high adherence (95%) in order to achieve drug effectiveness. However, compliance issues are still a major problem for PLWHA. Knowledge is one of many factors that can support adherence in therapy. This study aims to determine the correlation between the level of knowledge about HIV / AIDS, ARV therapy and opportunistic infections and the level of adherence of PLWHA in antiretroviral therapy. This study used a cross sectional total sampling method with a total sample of 50 respondents. The results of this study showed no significant relationship between the level of knowledge with the level of obedience of PLWHA in ARV therapy (p value = 0.107 > 0.05). These results contrast with the previous study who stated that there was a relationship between knowledge of ARV therapy and the level of obedience of PLWHA in undergoing ARV therapy in Padang Hospital.